Concordance of Organ Donation and Other Altruistic Behaviors Among Twins. (September 2019) - Huml, Anne M.; Thornton, J. Daryl; Figueroa, Maria; Cain, Katrice; Dolata, Jacqueline; Scott, Karen; Sullivan, Catherine; Sehgal, Ashwini R.
Introduction: Organ donation and other altruistic behaviors may be influenced by multiple factors, such as demographic characteristics, religious beliefs, and social norms. Research Question: What is the role of genetic factors on altruism in identical and fraternal twin pairs? Design: Twins attending a twin festival (N = 296) completed an organ donation and altruistic behavior survey. Results: Concordance for stage of change for organ donation was 65% among identical twin pairs versus 33% among fraternal twin pairs ( P = .004). Concordance was higher among identical versus fraternal twin pairs for several altruistic behaviors, including giving directions to a stranger (63% vs 24%, P < .001), giving money to a stranger (51% vs 29%, P = .048), donating goods to charity (46% vs 16%, P = .005), and offering a seat on the bus (46% vs 24%, P = .04). Discussion: We conclude that genetic factors may play a role in decisions about organ donation and other altruistic behaviors.